2016
DOI: 10.1111/add.13423
|View full text |Cite
|
Sign up to set email alerts
|

The burden of alcohol use disorders in US military veterans: results from the National Health and Resilience in Veterans Study

Abstract: More than 40% of US military veterans have a life-time history of alcohol use disorder. Veterans with a life-time history of alcohol use disorder have substantial comorbid psychiatric burden, including elevated rates of suicidal ideation and attempts. Certain socio-demographic (e.g. younger age, male sex, lower education) and clinical (e.g. trauma burden, history of depression) characteristics are associated with increased risk of AUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 54 publications
4
93
0
2
Order By: Relevance
“…AUDs were the most prevalent lifetime disorders among Ohio National Guard members (44%)(Fink et al, 2016a) and Canadian Regular Force members (32%)(Pearson et al, 2014). A contemporary survey of U.S. military veterans revealed that 42% had lifetime AUD and 15% had past-year AUD (Fuehrlein et al, 2016). Finally, there is evidence that deployments are associated with increased risk of new-onset AUDs (Jacobson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AUDs were the most prevalent lifetime disorders among Ohio National Guard members (44%)(Fink et al, 2016a) and Canadian Regular Force members (32%)(Pearson et al, 2014). A contemporary survey of U.S. military veterans revealed that 42% had lifetime AUD and 15% had past-year AUD (Fuehrlein et al, 2016). Finally, there is evidence that deployments are associated with increased risk of new-onset AUDs (Jacobson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A study of mental disorders in a representative sample of 671 Ohio Army National Guard members found that AUD was the most common lifetime disorder, with a prevalence of 44% (Fink et al, 2016a). U.S. military veterans also have a high prevalence (42%) of lifetime AUD (Fuehrlein et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Among veterans from the recent conflicts, of those seeking treatment at VA, 11% were diagnosed with a substance use disorder and 55 to 75% of those had comorbid PTSD (Seal et al., ). In a sample of veterans in the community, those with a lifetime history of alcohol use disorders had higher rates of both mood and anxiety disorders (Fuehrlein et al., ). Comorbidity is associated with a number of worse outcomes including higher rates of psychological problems, higher rates of relapse, hospitalizations, as well as medical and social complications such as unemployment and homelessness (Blanco et al., ; Drapkin et al., ; Ouimette et al., ).…”
mentioning
confidence: 99%
“…The NHRVS sample was drawn from a research panel of more than 50,000 households that is developed and maintained by GfK Inc., which maintains KnowledgePanel®, a probability-based, online non-volunteer access survey panel of a nationally representative sample of U.S. adults that covers approximately 98% of U.S. households, including cell-phone only households (see Fuehrlein et al, 2016 for detailed information on sampling procedures). GfK uses probability-based sampling of household addresses from the US Postal Service’s Delivery Sequence File, a method that allows for the inclusion of even those households with no telephone access.…”
Section: Methodsmentioning
confidence: 99%